2016
DOI: 10.2495/eid160021
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of sunflower husk ashes and feasibility analysis of their incorporation in soil and clay mixtures for ceramics

Abstract: The aim of this work is to study ashes from the combustion of sunflower husks in order to determine their environmental suitability for reuse as a structural filler or as an aggregate in clay mixtures for the manufacture of ceramics. Various characterization techniques were used, such as optical and electronic microscopy, X-ray electron dispersive analysis, X-ray diffraction, analysis of particle size distribution, soluble solids, conductivity, pH, leaching test and ecotoxicity, among others. The results of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Paleckiene et al (2012) in their study on obtaining fertilizer from rapeseed plant waste ash and sugar factory wastes found that rapeseed plant waste ash consists of 6.2% phosphorus element, 20.7% potassium element, 23.2% calcium element and 2.1% magnesium element Paleckiene et al (2012), in the study they conducted in order to determine the physical and chemical properties of the fertilizer obtained by adding various additives (sugar factory lime, molasses, urea formaldehyde resin) to the ash obtained from sunflower residues found that there were 10.94% P 2 O 5 , 25.84% K 2 O, 24.27% CaO, 19.07% MgO, 18.58% compounds in sunflower waste ash. Quaranta et al (2016), in their study of using ash obtained by burning sunflower husks in the production of ceramics or its re-use as a soil additive, found 15.6% Mg, 7.9% Ca, 4.8% P and 4.6% K in the content of sunflower husk ash. In a study on rapeseed plants in Poland, the chemical composition of the rapeseed waste ash was determined to be containing 15.1 g kg -1 phosphorus element, 155.7 g kg -1 potassium element, 124.0 g kg -1 calcium element and 7.3 g kg -1 phosphorus element (Piekarczyk et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Paleckiene et al (2012) in their study on obtaining fertilizer from rapeseed plant waste ash and sugar factory wastes found that rapeseed plant waste ash consists of 6.2% phosphorus element, 20.7% potassium element, 23.2% calcium element and 2.1% magnesium element Paleckiene et al (2012), in the study they conducted in order to determine the physical and chemical properties of the fertilizer obtained by adding various additives (sugar factory lime, molasses, urea formaldehyde resin) to the ash obtained from sunflower residues found that there were 10.94% P 2 O 5 , 25.84% K 2 O, 24.27% CaO, 19.07% MgO, 18.58% compounds in sunflower waste ash. Quaranta et al (2016), in their study of using ash obtained by burning sunflower husks in the production of ceramics or its re-use as a soil additive, found 15.6% Mg, 7.9% Ca, 4.8% P and 4.6% K in the content of sunflower husk ash. In a study on rapeseed plants in Poland, the chemical composition of the rapeseed waste ash was determined to be containing 15.1 g kg -1 phosphorus element, 155.7 g kg -1 potassium element, 124.0 g kg -1 calcium element and 7.3 g kg -1 phosphorus element (Piekarczyk et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the current research, the walnut shells ash (WSA) and sunflower ash (SFA) were acquired from the northern regions in Iraq. The WSA and SFA were put in oven at a 700 ± 50 °C for two hours according to the literature 51 . The ashes were cooled in an open area at room temperature for 30 min after being heated.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the recycling of these crusts through the usage in concrete as cement materials aids significantly in producing an environmentally friendly concrete and decreases cement usage. Nevertheless, previous attempts have been made to reuse both walnut shells as coarse or fine aggregate 47 – 50 and sunflower ash in micro size 51 , 52 within concrete. However, no previous research used walnut shells ash and sunflower ash at nano size.…”
Section: Research Significancementioning
confidence: 99%
“…Energies 2020, 13, x FOR PEER REVIEW 8 of 15 component to produce fertilizer [52]. Moreover, it is suitable as a filler for the production of ceramics [53]. Its price is more than EUR80/t.…”
Section: Energy Supply System Based On Biomassmentioning
confidence: 99%